2016
DOI: 10.1007/978-3-319-44509-0_9
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic and Utilitarian Effects of the Adoption and Use of Social Commerce

Abstract: The aim of this research is to contribute to the field of study which explores the consumer behaviour model in social commerce, introducing the social commerce concept as a new commercial formula. To study the acceptance and use of social commerce by consumers, we have proposed the Social Commerce Acceptance Model which brings together several models of technology acceptance, including the Technology Acceptance Model (TAM), its successor Technology Acceptance Model 2 (TAM2) and The Unified Theory of Acceptance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
(70 reference statements)
3
7
0
1
Order By: Relevance
“…This result suggests that, to increase perceived value, the MAA content must convince consumers of the potential advantages of shopping for fashion products through the branded mobile app (e.g., saving time and money, providing incentives). This result complements recent studies [100,101] that also demonstrated that perceived usefulness is a key driver of the perceived value of branded mobile apps. Ease of use had a strong impact on perceived usefulness (H4b accepted, β = 0.791**), confirming the TAM proposition [36].…”
Section: Resultssupporting
confidence: 88%
“…This result suggests that, to increase perceived value, the MAA content must convince consumers of the potential advantages of shopping for fashion products through the branded mobile app (e.g., saving time and money, providing incentives). This result complements recent studies [100,101] that also demonstrated that perceived usefulness is a key driver of the perceived value of branded mobile apps. Ease of use had a strong impact on perceived usefulness (H4b accepted, β = 0.791**), confirming the TAM proposition [36].…”
Section: Resultssupporting
confidence: 88%
“…Table 1 shows how previous studies have used the three foundational elements of SC including social, technological and personal trait aspects to develop a model toward understanding user intention to use and engage with the online community. Meanwhile, the personal trait was observed to have dominated the underlying framework used by most previous studies to propose the theoretical model (Kim and Park, 2013;Pöyry et al, 2013;Kabadayi and Price, 2014;Chow, 2015;Kim, 2015;Farivar et al, 2017;Hajli et al, 2017;Sharma et al, 2019;Zha et al, 2019;Wang et al, 2019;Vohra and Bhardwaj, 2019;Pelletier et al, 2020;Corrêa et al, 2020) followed by social aspect (Hajli, 2014;Shao and Ross, 2015;Shanmugam et al, 2016;Lu et al, 2016;Gibreel et al, 2018;Kucharska, 2019;Xue, 2019;Handarkho, 2020aHandarkho, , 2020b and social technology aspect (Shin, 2013;Featherman and Hajli, 2015;Han et al, 2016;Plaza-Lora and Villarejo-Ramos, 2017;Clark et al, 2017). Some others have also combined and integrated social aspect with technology or personal trait element (Sharma and Crossler, 2014;Chen and Shen, 2015;Liebana-Cabanillas and Alonso-dos-Santos, 2017;Lal, 2017;Gibreel et al, 2018;Handarkho, 2020aHandarkho, , 2020b while those from the marketing field have made use of the three to study users' intention toward the SC platform and their effect on social interaction engagement (Kabadayi and Price, ...…”
Section: Overview Of Previous Studiesmentioning
confidence: 99%
“…as the dependent variable. Moreover, several studies have successfully used accepted technology adoption models such as TAM (Plaza-Lora and Villarejo-Ramos, 2017;Featherman and Hajli, 2015;Shin, 2013), as well as theories based on social influence (Handarkho, 2020a(Handarkho, , 2020bYang, 2019;Liebana-cabanillas and Alonso-dos-santos, 2017;Shanmugam et al, 2016), trust (Kim and Park, 2013;Kabadayi and Price, 2014;Chow, 2015;Farivar et al, 2017;Sharma et al, 2019;Vohra and Bhardwaj, 2019;Vohra and Bhardwaj, 2019) and the stimulus-organism-response (Kim, 2015;Zhang et al, 2014) to develop a theoretical model. This present research, however, explicitly used social impact theory as the fundamental basis for social interaction followed by social exchange theory for the personal trait, and TAM and ISSM for the social technology aspect.…”
Section: Social Commercementioning
confidence: 99%
See 2 more Smart Citations